POLITENESS IN USING PAKPAKNESE IN PERSONAL SUBJECT PRONOUNS IN DAILY CONVERSATION AT JAMBU MBELLANG - Pricilia Pricilia; Sri Minda Murni; Sisilia Fitriany Damanik (LINGUISTICA, 2019)
This descriptive qualitative research deals with the Politeness in Using Pakpaknese in Personal Subject Pronouns in Daily Conversation at Jambu Mbellang. The problem of the study were to find the (1)types of politeness in using Pakpaknese in personal subject pronouns show daily conversation, (2)how to personal subject pronouns show daily conversation and (3)why Pakpak people need to show personal subject pronoun by Pakpaknese. The data were collected by taken 30 people (15 male and 15 female) at Jambu Mbellang District as respondent/participant were collected by using questionnaire, recording the daily conversation of Pakpaknese people,the last data the researcher  used interview and then were transcribed. The data were analyzed by qualitative research based on Brown and Levinson. The result of the research shown that second types of politeness show pakpaknese,how do Pakpak people show personal subject pronouns and why Pakpak people need show personal subject pronouns. The analyzed of  questionnaire that speaker male speak to male the equal language were often used and in the speaker male speak female the younger language were often used. In the speaker of female speak female show younger language to used communication and female speak male the older language were often used. types of politeness in show PSP, on record the answer how Pakpak people show PSP that conversation found four speech function , and used interview found intimacy, politeness, relation, adapting situation into ever conversation in Pakpak why Pakpak people need to show PSP.Keywords : pakpaknese, personal pronouns, politeness,